A survey of deepwater horizon (DWH) oil-degrading bacteria from the Eastern oyster biome and its surrounding environment - Thomas, Jesse C.; Wafula, Denis; Chauhan, Ashvini; Green, Stefan J.; Gragg, Richard; Jagoe, Charles (Frontiers in Microbiology, 2014)
The Deepwater Horizon (DWH) accident led to the release of an estimated 794,936,474 liters of crude oil into the northern Gulf of Mexico over an 85 day period in 2010, resulting in the contamination of the Gulf of Mexico waters, sediments, permeable beach sands, coastal wetlands and marine life. This study examines the potential response of the Eastern oyster’s microbiome to hydrocarbon contamination and compares it with the bacterial community responses observed from the overlaying water column and the oyster bed sediments. For this purpose, microcosms seeded with DWH crude oil were established and inoculated separately with oyster tissue (OT), mantle fluid (MF), overlaying water column (WC) and sediments (S) collected from Apalachicola Bay, FL. Shifts in the microbial community structure in the amended microcosms was monitored over a 3-month period using automated ribosomal intergenic spacer region analysis (ARISA), which showed that the microbiome of the oyster tissue and mantle fluid were more similar to the sediment communities than those present in the overlaying water column. This pattern remained largely consistent, regardless of the concentration of crude oil or the enrichment period. Additionally, 72 oil-degrading bacteria were isolated from the microcosms containing OT, MF, WC and S and identified using 16S ribosomal RNA (rRNA) gene sequencing and compared by principal component analysis (PCA) which clearly showed that the water column isolates were different to those identified from the sediment. Conversely, the oyster tissue and mantle fluid isolates clustered together; a strong indication that the oyster microbiome is uniquely structured relative to its surrounding environment. When selected isolates from the OT, MF, WC and S were assessed for their oil-degrading potential, we found that the DWH oil was biodegraded between 12%-42%, under the existing conditions.